Sustainable solid waste management : issues, policies, and structures - Dhamija, Urvashi (New Delhi : Academic Foundation, 2006)
With reference to Delhi, India.
Includes statistics.
H.B
Includes bibliographical (p. [247]-252) references and index.
Keywords: Refuse and refuse disposal -- India -- Delhi; Recycling (Waste etc.) -- India -- Delhi